Antynomie Trzeciego w myśli Emmanuela Lévinasa - Kalaga , Wojciech (Przestrzenie Teorii, 2020)
The ethics of Emmanuel Lévinas – the idea of asymmetrical, unconditional responsibility for and devotion to the Other – is founded on the dichotomy between the Same (I) and the Other. The objective of the article is to demonstrate that, in spite of this dichotomous foundation, Lévinas’s argument paradoxically eludes the binary logic of the Western logos. Employing the ‘close reading’ method with Otherwise than Being or Beyond Essence, the author shows how Lévinas’s way of thinking and the main concepts of his argument situate themselves beyond binary oppositions – in the realm of the excluded middle or, otherwise, in the realm of the Third, construed as transgression of dichotomies. The main argument is preceded by a discussion of the antinomies introduced into the I-Other relation by the appearance of the Third construed as the Third Party (le tiers).